Integrative medical approaches to allergic rhinitis. Issue 3 (June 2015) - Asher, Benjamin F.; Seidman, Michael D.; Reddy, William D.; Omole, Folashade S.
Abstract : Purpose of review: Complementary and integrative medicine (CIM), formerly known as alternative medicine, is now part of the mainstream management for patients with a host of medical issues. This current opinion focuses on the use of CIM, more specifically, the use of nutritional and herbal therapies and homeopathic medications for patients with allergic symptoms. Recent findings: The literature review revealed that naturally occurring substances when compared with placebo more often than not resulted in significant improvement of the allergic rhinitis symptoms. Summary: Despite encouraging results, additional studies with greater rigor are needed.